Neurological outcome in adult out-of-hospital cardiac arrest – Not all doom and gloom!. (October 2021) - Mckenzie, Nicole; Ball, Stephen; Bailey, Paul; Finn, Lyndall; Arendts, Glenn; Celenza, Antonio; Fatovich, Daniel; Jenkins, Ian; Mukherjee, Ashes; Smedley, Ben; Ghedina, Nicole; Bray, Janet; et al.
Abstract: Aims: To describe neurological and functional outcomes among out-of-hospital cardiac arrest (OHCA) patients who survived to hospital discharge; to determine the association between neurological outcome at hospital discharge and 12-month survival. Methods: Our cohort comprised adult OHCA patients (≥18 years) attended by St John WA (SJWA) paramedics in Perth, Western Australia (WA), who survived to hospital discharge, between 1st January 2004 and 31st December 2019. Neurological and functional status at hospital discharge (and before the arrest) was determined by medical record review using the five-point 'Cerebral Performance Category (CPC)' and 'Overall Performance Category (OPC)' scores. Adjusted multivariable logistic regression analysis was used to estimate the association of CPC score at hospital discharge with 12-month survival, adjusted for prognostic variables. Results: Over the study period, SJWA attended 23, 712 OHCAs. Resuscitation was attempted in 43.4% of cases (n = 10, 299) with 2171 subsequent admissions, 99.4% (n = 2158) of these were admitted to a study hospital. Of the 1062 hospital survivors, 71.3% (n = 757) were CPC1 (highest category of neurological performance), 21.4% (n = 227) CPC2, 6.3% (n = 67) CPC3 and 1.0% (n = 11) CPC4. OPC scores followed a similar distribution. Of the 1, 011 WA residents who survived to hospital discharge, 92.3% (n = 933) survived to 12-months. A CPC1-2 at hospital discharge was significantly associated with 12-month survival (adjusted odds ratio 3.28, 95% confidence interval 1.69–6.39). Conclusion: Whilst overall survival is low, most survivors of OHCA have a good neurological outcome at hospital discharge and are alive at 12-months.